Combined effect of steel fibres and steel rebars on impact resistance of high performance concrete - Chen, Xiang-yu; Ding, Yi-ning; Azevedo, C. (Journal of Central South University, 2011)
The impact properties of normal concrete (NC) and reinforced concrete (RC) specimens, steel fibre reinforced concrete (SFRC) specimens and RC+SFRC specimens with different steel fibre dosages were investigated with the drop-weight impact test recommended by ACI Committee 544. The results indicate that the number of blows to final failure is greatly increased by addition of steel fibres. Moreover, the combination of steel fibres and steel rebars demonstrates a significant positive composite effect on the impact resistance, which results in the improvement in impact toughness of concrete specimens. In the view of variation of impact test results, the two-parameter Weibull distribution was adopted to analyze the experimental data. It is proved that the probabilistic distributions of the blows to first crack and to final failure of six types of samples approximately follow two-parameter Weibull distribution.